Incidence of transient interruption of contrast (TIC): a retrospective single-centre analysis in CT pulmonary angiography exams acquired during inspiratory breath-hold with the breathing command: “Please inspire gently!” - Janssen, Sonja; Haubenreisser, Holger; Henzler, Thomas; Schönberg, Stefan (PLOS ONE, 2019)
Objectives To assess the occurrence of transient interruption of contrast (TIC) phenomenon in pulmonary computed tomography angiography (CTPA) exams performed in inspiratory breath-hold after patients were told to inspire gently. Methods In this retrospective single-centre study, CTPA exams of 225 consecutive patients scanned on a 16-slice CT scanner system were analysed. A-priori to measurements, exams were screened for inadequate pulmonary artery contrast due to incorrect bolus tracking or failure of i.v. contrast administration. Those exams were excluded. Attenuation values in the thoracic aorta and in the pulmonary trunk were assessed in duplicate measurements (M1 and M2) and the aorto-pulmonary density ratio was calculated. An aorto-pulmonary ratio > 1 with still contrast inflow being visible within the superior vena cava was defined as TIC. Results 3 patients were excluded due to incorrect bolus tracking. Final analysis was performed in 222 patients (mean age 65 ± 19 years, range 18 to 99 years). Mean density in the pulmonary trunk was 275±17 HU, in the aorta 208 ± 15 HU. Mean aorto-pulmonary ratio was 0.81± 0.29. 48 patients (21.6%) had an aorto-pulmonary ratio >1. Correlation of mean aorto-pulmonary ratio and age was: -0.213 (p = 0.001). Age was not significantly different for an aorto-pulmonary ratio >1 vs. ≤1 (p = 0.122). Both in M1 and M2, 33/222 patients presented with absolute HU values of < 200 HU within the pulmonary artery. In M1 measurements, 24 of these 33 patients (72%) fulfilled TIC criteria (M2: 25/33 patients (75%)). Conclusions TIC is a common phenomenon in CTPA studies with inspiratory breath-hold commands after patients were told to inspire gently with an incidence of 22% in our retrospective cohort. Occurrence of TIC shows a significant negative correlation with increasing age and disproportionately often occurs in patients with lower absolute contrast density values within their pulmonary arteries.